Are Anticholinergic Medications Associated With Increased Risk of Dementia and Behavioral and Psychological Symptoms of Dementia? A Nationwide 15-Year Follow-Up Cohort Study in Taiwan - Liu, Yia-Ping; Chien, Wu-Chien; Chung, Chi-Hsiang; Chang, Hsin-An; Kao, Yu-Chen; Tzeng, Nian-Sheng (Frontiers in Pharmacology, 2020)
Background/objective In previous reports, the usage of anticholinergic medications has been associated with an increased risk of dementia with prolonged usage or with a high Anticholinergic Cognitive Burden (ACB). This study aimed to investigate the association between anticholinergic medications and the risk of dementia using data from Taiwan’s National Health Research Database (NHIRD). Methods A total of 790,240 patients, with 197,560 patients receiving anticholinergic medications and 592,680 control patients (1:3) matched for sex, age, and index-year, were enrolled from the two million Longitudinal Health Insurance Dataset, a subdataset of the NHIRD, between 2000 and 2015. The time-dependent Cox regression analysis was used to explore the hazard ratio (HR) with a 95% confidence interval for the association between anticholinergics and the risk of dementia during the 15-year follow-up. The behavioral and psychological symptoms of dementia (BPSD) were recognized by the usage of psychotropics. The ACB ranged from zero to three, divided as score <1, 1-1.9, 2-2.9, 3-4.9,and ≧5. The sensitivity analysis was done by excluding the diagnoses of dementia in the first two or four years after anticholinergic usage. Results In the anticholinergic usage cohort, the HR was 1.043 (95% CI = 0.958-1.212 , p = 0.139) without a significant difference. The sensitivity analysis revealed no association between the usage of anticholinergics and the risk of dementia. Anticholinergic usage was not associated with BPSD. Male sex, patients of ages of 60-64 and ≧80 , usage of antiparkinsonian medications, a history of Parkinson's disease, epilepsy, urinary incontinence, depression, bipolar disorder, and psychotic disorder were independent risk factors of dementia. Increased HRs for dementia were associated with an ACB ≥ 5 and an anticholinergic usage period ≥ 1460 days. Conclusion In this study, the usage of anticholinergics was not associated with the risk of dementia or BPSD in a 15-year follow-up study. However, patients with the male sex, patients with ages of 65-79 and ≧80, patients with some comorbidities, high ACB scores, and long anticholinergic treatment duration were associated with the risk of dementia.